Topics in Broadband Gravitational-Wave Astronomy - (:unkn) unknown (My University, 2015)
The direct detection of gravitational waves promises to open a new observational window onto the universe, and a number of large scale efforts are underway worldwide to make such a detection a reality. In this work, we attack some of the current problems in gravitational-wave detection over a wide range of frequencies. In the first part of this work, low frequency gravitational-wave detection is considered using pulsar timing arrays (PTAs). PTAs are a promising tool for probing the universe through gravitational radiation. Supermassive black hole binaries (SMBHBs), cosmic strings, relic gravitational waves from inflation, and first order phase transitions in the early universe are expected to contribute to a stochastic background of gravitational waves in the PTA frequency band of 1 nHz-100 nHz. The detection of low-frequency stochastic backgrounds of gravitational waves in the PTA band is considered in the context of constructing an optimal cross-correlation statistic in the time domain. Also presented are some useful applications of this statistic, and discussion on its limitations in actual gravitational-wave searches. Also considered are methods by which gravitational waves in the PTA frequency band can serve as a mechanism for testing general relativity (GR). In addition to providing a new paradigm for exploring the universe, the direct detection of gravitational waves will allow general relativity to be tested against other metric theories of gravity in the regime of strong gravitational fields. This work involves the analysis of the overlap reduction function (ORF), a geometrical factor that appears in the expected cross correlation of signals, for general metric theories of gravity. The ORF characterizes the loss of sensitivity due to detectors not being co-located or coaligned, and it is an important element in defining the optimal cross-correlation statistic. It is shown that PTA detection sensitivity increases for non-transverse gravitational waves. Additionally, the ORFs for a subset of the NANOGrav PTA are described, and are used to show that sensitivity to vector and longitudinal modes can increase dramatically for pulsar pairs with small angular separations. Implications of these results are discussed. In the second part of this work, the detection of gravitational-wave bursts in the 10 Hz-1000 Hz frequency band is considered using ground-based laser interferometers. An excess power method for conducting unmodeled searches for gravitational-wave bursts is discussed, and its implementation into a search pipeline is described in detail. The performance of this pipeline is probed using software injections. Also discussed are potential applications of the ExcessPower pipeline to detector characterization efforts, which aim to improve interferometric searches by characterizing and mitigating non-Gaussian noise transients in the detectors.
Keywords: Data Analysis; Gravitational Waves